Mucopolisacaridosis tipo VI (síndrome Maroteaux-Lamy) en la cultura precolombina de Colombia (2014)
Mucopolysaccharidosis type VI or Maroteaux Lamy syndrome is an autosomal recessive lysosomal storage disorder resulting from a deficiency of arylsulfatase B, the clinical features include short stature, hepatosplenomegaly, dysostosis multiplex, stiff joints, corneal clouding, cardiac abnormalities, and facial dysmorphism, with intelligence usually normal. We present evidence of the possible existence of Maroteaux Lamy syndrome in pre-Columbian pottery 2000 years ago, in the Colombo-Ecuadorian Pacific coast of the Tumaco-Tolita culture.